1998
DOI: 10.1177/135245859800400606
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus-6 (HHV-6) infection in multiple sclerosis: a preliminary report

Abstract: We examined cerebral spinal fluid (CSF) from multiple sclerosis (MS) patients and patients with other neurological diseases (OND) for antibody specific for Human Herpesvirus-6 (HHV-6) and for HHV-6 DNA detectable by PCR. CSF from MS patients had a higher frequency of IgG antibody to HHV-6 late antigens (39.4%) compared with CSF from OND (7.4%). In contrast, the frequency of detectable IgG antibody in CSF from MS patients specific for Epstein-Barr Virus (EBV) (12.1%) and Human Cytomegalovirus (HCMV) (6.1%) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 26 publications
3
51
0
Order By: Relevance
“…19,20 Two studies were classified as B quality. 24,25 Ongradi et al 24 reached statistical significance and reported only "high" and "low" antibody titers in MS patients and controls without providing actual values, whereas Ablashi et al 25 did not find significant differences in titers.…”
Section: Serologic Studiesmentioning
confidence: 98%
See 4 more Smart Citations
“…19,20 Two studies were classified as B quality. 24,25 Ongradi et al 24 reached statistical significance and reported only "high" and "low" antibody titers in MS patients and controls without providing actual values, whereas Ablashi et al 25 did not find significant differences in titers.…”
Section: Serologic Studiesmentioning
confidence: 98%
“…18,19 Four studies were classified as intermediate quality (B), and none of them showed a statistically significant difference between MS patients and controls. 20,[24][25][26] One of those studies considered mean antibody titers, 20 and another reported only that the IgG titers of MS patients were higher than those of controls without providing absolute values. 24 The remaining 7 studies were classified as lower quality (C), mostly because of a failure to define and provide details about the study patients with MS. [21][22][23]27,[29][30][31] According to the CTF classification, 18 of the 18 studies were classified as quality II-1.…”
Section: Serologic Studiesmentioning
confidence: 99%
See 3 more Smart Citations